Perlindungan Hukum Terhadap Anak Sebagai Tukang Parkir Di Kota Sorong - Barru, Agustina Arusano Gloria; Mahmudah, Masrifatun; Lestaluhu, Rajab (Journal of Law Justice (JLJ), 2023)
This research aims to know the child labour riviewed by indonesian law . To find out about protection of law Against child work as a parking attendant in Sorong City. The research method used in this research is Empirical research using method approach Abstract law sociology, The research specs used in this research Is descriptive analysis, processing of the data used primary data collection techniques who are observation and interview. Research results shows that there is no legal protection against The Child who works as a parking attendant in Sorong City. Sorong city administration has not made regulation towards The Children who works in general and specifically children who work as a Parking Attendant